A formação do educador em educação musical : os desafios e as pertinências à inclusão da pessoa com deficiência - Araujo Junior, Rusiel Paulino de (2019)
Driven by personal and professional responsibility as a music educator and the socio-historical and scientific relevance of education studies aimed at people with disabilities, we developed a study on the education of music education teachers, from an investigative look at the Music Education Course from Universidade Federal da Paraíba (UFPB). This thesis is composed of four chapters that discuss, discuss and analyze interviews, questionnaires and the current pedagogical project of the course in focus, proposing, at the end, a guideline, however preliminary, of how to introduce an inclusive vocational training. We start from the methods of analysis and criticism built on the Educational Policies line of the Postgraduate Program in Education of UFPB, in order to continue the previous study on the teacher education of the music educator, developed as a Master's dissertation. To this end, we agree to make our contribution to this critique and academic studies in general by adopting the stance and approach of research in education of some theorists who we think are pointing in the most assertive and rational direction, being Paulo Freire. , Libânio, Moreira and Candau, Mazzotta, Barbosa, Fonterrada, Boaventura, Penna, Queiroz, Schafer, among others, as well as institutional documents and laws. In addition to the theoretical argumentation, we seek, in this work, to conduct an empirical study, using theoretical and field research, in order to produce scientific knowledge and an academic discourse around the researched theme; and provide a dialogue between the knowledge we intended to produce and the knowledge that came to us through the participants and collaborators of this research. Our object of study, music education, as a pedagogical project and from inclusive practical activities, will result as a pedagogical instrument of schools; it is a rich and challenging field, reinforcing our convictions about the need for a democratic and inclusive school capable of dialogue with different cultures.